2022
DOI: 10.1590/0004-282x-anp-2021-0080
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-weighted imaging as predictor of acute ischemic stroke etiology

Abstract: Background: Topographic patterns may correlate with causes of ischemic stroke. Objective: To investigate the association between diffusion-weighted imaging (DWI) and Trial of Org 10172 in Acute Stroke Treatment (TOAST) classification. Methods: We included 1019 ischemic stroke patients. DWI were classified as: i) negative; ii) DWI single lesion (cortico-subcortical, cortical, subcortical ≥20 mm, or subcortical <20 mm); iii) scattered lesions in one territory (small scattered lesions or confluent with addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
(38 reference statements)
0
4
0
1
Order By: Relevance
“…By assisting with a diagnosis of SVD, MRI DWI could improve secondary stroke prevention by focusing management on addressing vascular risk factors and potentially avoid additional tests that will not likely change management. Prior studies have demonstrated that infarct topography is useful to identify an ischemic etiology, 7 , 8 , 9 , 10 , 11 , 12 while the present study demonstrates the potential magnitude of using this tool to reduce the rate of cryptogenic etiology in the TIA or minor stroke population.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…By assisting with a diagnosis of SVD, MRI DWI could improve secondary stroke prevention by focusing management on addressing vascular risk factors and potentially avoid additional tests that will not likely change management. Prior studies have demonstrated that infarct topography is useful to identify an ischemic etiology, 7 , 8 , 9 , 10 , 11 , 12 while the present study demonstrates the potential magnitude of using this tool to reduce the rate of cryptogenic etiology in the TIA or minor stroke population.…”
Section: Discussionmentioning
confidence: 55%
“…This result is consistent with a prospective study of patients with acute ischemic stroke, where a single subcortical lesion was strongly associated with increased odds of lacunar stroke diagnosis. 12 Although SVD can be diagnosed clinically on the basis of presence of symptoms suggestive of a classic lacunar syndrome, SVD diagnosis also depends on brain imaging. Visualizing a single, small, subcortical lesion on DWI likely increases the clinician's confidence of attributing the etiology to SVD, and, conversely, identifying multiple infarcts would decrease the attribution to small‐vessel etiology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nghiên cứu của chúng tôi cũng ghi nhận tỷ lệ nhồi máu não vùng vỏ-dưới vỏ cao hơn ở nhóm có huyết khối tiểu nhĩ trái so với nhóm không có. Kết quả này cũng đã được ghi nhận trong nghiên cứu của Alejandro và cộng sự với cơ chế chính xác chưa được hiểu rõ mặc dù có thể liên quan đến vị trí tắc động mạch và mức độ lan rộng của tổn thương não do huyết khối từ tim [16].…”
Section: đặC đIểm Tổn Thương Não Trên Cộng Hưởng Từ ở Bệnh Nhân Cao T...unclassified
“…In addition, DWI can differentiate between ischemic and hemorrhagic subtypes of stroke since hemorrhagic stroke often does not exhibit diffusion-restricted areas on DWI images (Brunser et al, 2022) (Yoo et al, 2011). The grayscale values and diffusion indices of DWI images can be used to assess functional prognosis of stroke patients (Bang et al, 2005).…”
Section: Diffusion-weighted Imagingmentioning
confidence: 99%